2019
DOI: 10.1002/dvdy.25
|View full text |Cite
|
Sign up to set email alerts
|

FoxN3 is necessary for the development of the interatrial septum, the ventricular trabeculae and the muscles at the head/trunk interface in the African clawed frog, Xenopus laevis (Lissamphibia: Anura: Pipidae)

Abstract: Background Fox genes are a large family of transcription factors that play diverse roles in the immune system, metabolism, cancer, cell cycle, and animal development. It has been shown that FoxN3 is indispensable for normal craniofacial development in the mouse and the African clawed frog, Xenopus laevis. Morpholino‐mediated knockdown of FoxN3 in X. laevis delays overall development of early tadpole stages and causes eye defects, the absence of some cranial nerve branches, and malformations of the cranial ske… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 63 publications
(179 reference statements)
0
2
0
Order By: Relevance
“…These signaling pathways may regulate cell fate choices within a pool of progenitor cells primed for heart and head muscle fates rather than acting on individual bipotent cells. Finally, work in Xenopus has shown that the transcription factor FoxN3 is required in the anuran branchiomeric neck muscle program as well as for development of the venous pole of the heart, although the underlying mechanisms remain to be resolved [87].…”
Section: Cardiopharyngeal Mesoderm In Ciona and Zebrafishmentioning
confidence: 99%
“…These signaling pathways may regulate cell fate choices within a pool of progenitor cells primed for heart and head muscle fates rather than acting on individual bipotent cells. Finally, work in Xenopus has shown that the transcription factor FoxN3 is required in the anuran branchiomeric neck muscle program as well as for development of the venous pole of the heart, although the underlying mechanisms remain to be resolved [87].…”
Section: Cardiopharyngeal Mesoderm In Ciona and Zebrafishmentioning
confidence: 99%
“…Chromatin Immunoprecipitation (ChIP)-seq and structural analysis found that CHES1 was a bispecific transcription factor which recognized a canonical forkhead (FKH) motif as well as alternate lower affinity (FHL) motif simultaneously [ 19 , 20 ]. Functionally, CHES1 modulated many cellular procedures, such as cell cycle arrest [ 15 , 21 ], embryogenesis [ 22 , 23 ], glucose metabolism [ 24 ], insulin sensitivity [ 25 ] and DNA damage response [ 16 ]. Moreover, the regulatory role of CHES1 has been established in various malignancies, and its dysfunction has been associated with outcome of patients [ 26 , 27 ].…”
Section: Introductionmentioning
confidence: 99%